Introduction to management equity in the Iranian health system with Physician-center approach - Pezhman Bagheri (مدیریت اطلاعات سلامت, 2014)
Despite the changes that have been made in recent years in the field of health, health systems Experts believe that the development of management is the major challenges of health systems. Improving the management of health organizations, have different approaches, such as quality management, health Dynamic networks, management effective program and  network comprehensive has been test. But the basic approach and the missing link in this vicious cycle namely insist on Physician-centered process in      the central management of health and care system, have neglected from the practitioner's point of view, researchers and policy makers. In the developing countries it is not interest to contribute to professional managers to manage health care organization. Hence, It seems that one of the most important challenges of the current health care system, be lack of fitness and accountability and a lack of structured system of manager choice in this realm. This is a narrative review that attempts with review of existing evidences and expert opinion in the field of health systems to Coordinate Physician-centered issue for informing policy makers of the country's macroeconomic management, the need for extreme care in regard to the issue management system and its emphasis. The findings suggest that our current health care system is Suffering of Excessive rust physician governance and to grow and overcome to the its major problem, need to make major changes in your current management system. Accordingly, it seems achieving to the goal of improving the management of Physician-centered health care system needs to factors such as Formulation, implementation and evaluation of pilot projects, policy development for the pilot results, capacity building, education and empowerment. Keywords: Justic; Management; Health Care Systems; Iran